Service Quality and Its Impact on Consumer Satisfaction - HERMAN, HERMAN (Adpebi International Journal of Multidisciplinary Sciences, 2023)
One of the reasons a company continues to exist is because of its ability to satisfy consumers. Satisfied consumers will survive while those who are dissatisfied will move elsewhere. This study aims to determine the effect of the quality of services provided by PT. New Inti Furnindo for customer satisfaction. The population in this study were 10,338 consumers who shopped at PT. New Inti Furnindo Pekanbaru. Thus the number of samples is 99 consumers. From the results of the analysis it can be concluded that service quality has a significant effect on customer satisfaction at PT. New Inti Furnindo Pekanbaru. The value of R square (R2) was obtained at 0.623 or 62.3% while 37.7% was influenced by other variables that were not in this study.Keywords:Service Quality, Customer Satisfaction